NATIONAL GAMES OF THE UZBEK PEOPLE AND THEIR PECULIARITIES - Akhmedova Nozimakhon (Journal of new century innovations, 2024)
Abstract: the national games of the Uzbek people have a long past, a rich history, are passed down from ancestors to generations, and are considered one of our spiritual wealth and values. Since the first days of our country’s independence, great attention has been paid to the restoration of our national values, traditions and customs, including folk games. This article will tell about Uzbek national games and their peculiarities. Z is maintained.